Effects of Ghrelin plasmid on growth performance and circulating GH, IGF-I, and SS in weaning piglets - CAI, ZHANG; WEN-YAN, YANG; CHUN-YIN, GENG; JIA-JIA, LIU; DE-LI, LI; XIN, ZHENG; LIAN-YU, YANG (The Indian Journal of Animal Sciences, 2012)
The aim of this study was to investigate effects of ghrelin plasmid (PCI-ghrelin-28aa) administration on plasma growth hormone (GH), insulin-like growth factor-I (IGF- I), and somatostatin (SS) levels, and growth performance in weaning pigs. Number I Junmu weaning piglets (8), 45-day-old, were randomly placed into 2 groups. Pigs in treatment groups were injected intra-muscularly with 1.5 mg kg-1 of ghrelin plasmid and in the control group, same dose of elution buffer. On day 0, 7, 21, 35, 49, and 63, body weight, food intake, and the circulating levels of GH, IGF-I, and SS were measured. The results showed that ghrelin plasmid significantly increased average daily weight gain (ADG) by 10.45% at 21 to 35 days. There were no significant differences between the treatment and control groups for daily food intake. Feed gain ratio (F/G) for the ghrelin treatment group was significantly better than control at 21–35d and 0–63d. Serum GH concentrations were significantly higher than control at 35 and 49 days. IGF-I levels were higher at 7 to 35 days in treated piglets and then decreased to a value which was significantly lower than those of the controls at 63 days. SS increased by 14% at 35 days and by 50% at 63 days. Results indicated that Ghrelin plasmid increased ADG and F/ G, and regulated the levels of GH, IGF-I, and SS in piglets.